A new Compsodactylus Fuhrmann (Coleoptera: Scarabaeidae: Melolonthinae) from Peru - Figueroa, Luis; Neita-Moreno, Jhon César (Zootaxa, 2019)
The tribe Macrodactylini (Coleoptera: Scarabaeidae: Melolonthinae) is distributed throughout the world, comprising approximately 1028 species and 80 genera; the majority of genera are found in the Neotropical Region, where 46 genera occur (Katovich 2008; Fuhrmann 2012; Smith & Mondaca 2015; Fuhrmann & Vaz-de-Mello 2017).